PENERAPAN SISTEM INFORAMASI PERIZINAN KARYAWAN BERBASIS WEB DI CV. DUTA JEPARA (Science and Technology (SciTech), 2022)
An information system is a component that is interconnected and functions to collect, process, store and distribute complete information as a reference to support decision making and control within the organization. The process of applying for a permit at the company CV. Duta Jepara is still done manually, resulting in an inefficient and ineffective permit application process with a large number of employees, of course, personnel will have difficulties in the process of recording and managing permits where permit data is vulnerable to errors in inputting and searching for data. Given the advancement of technology that is increasingly advanced, of course it will be very easy and helpful in a job. Data collection in this study uses the method of Observation, Interview, Documentation and Literature Study as well as in making Web applications using the Waterfall method with stages of analysis, design, coding, testing, implementation and maintenance using the PHP programming language, Laravel Framework and MySQL database as well as graphical modeling. using Unified Modeling Language (UML) with testing using BlackBox Testing, Expert Validation and Questionnaires. The results of the test for media and material experts get 96% and the questionnaire gets 95.7% while for blackbox testing it is valid. From the three types of testing, the researcher concludes that the Web-based employee permit information system at CV. Duta Jepara Very Eligible to apply because it meets all the eligibility criteria.